2011
DOI: 10.1002/eco.146
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate response to stream restoration by large wood addition

Abstract: We examined the aquatic macroinvertebrate community response to habitat rehabilitation activities in an incised, sand-bed stream. Seventy-two large wood (LW) structures were placed along 2 km of Little Topashaw Creek (37 km 2 watershed) in north-central Mississippi, USA. Macroinvertebrate collections were made from bed sediments, LW, leaf packs and qualitative multi-habitat sampling during 2 years prior to and 2 years following LW addition. Addition of LW tripled the availability of wood substrate but had no m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 83 publications
(96 reference statements)
0
13
1
Order By: Relevance
“…However, a review of the available stream-restoration literature conducted in 2010 indicated that macroinvertebrate biodiversity was not typically enhanced by the restoration of in-stream habitat, at least over time scales of <10 or 20 y (Palmer et al 2010). Studies published since that review continued to indicate that stream restoration efforts, including the addition of wood, often have no measurable effect on macroinvertebrate richness (e.g., Louhi et al 2011, Testa et al 2011.…”
mentioning
confidence: 94%
“…However, a review of the available stream-restoration literature conducted in 2010 indicated that macroinvertebrate biodiversity was not typically enhanced by the restoration of in-stream habitat, at least over time scales of <10 or 20 y (Palmer et al 2010). Studies published since that review continued to indicate that stream restoration efforts, including the addition of wood, often have no measurable effect on macroinvertebrate richness (e.g., Louhi et al 2011, Testa et al 2011.…”
mentioning
confidence: 94%
“…A few studies on drifting invertebrate biomass showed no change due to addition or removal of stream wood (Siler et al, 2001, for FW;Gustafsson, 2011, for LW). On the other hand, taxonomic diversity of stream invertebrates is generally higher in habitats where large or fine wood is present (Gerhard & Reich, 2000;Hernandez et al, 2005;Lester et al, 2007; but see Liljaniemi et al, 2002;Testa et al, 2011), and this may be particularly pronounced if other stable substrates are lacking Pitt & Batzer, 2011;Pilotto et al, 2014). Studies of invertebrate drift in relation to wood are rare.…”
Section: Introductionmentioning
confidence: 95%
“…Robinson et al, 2004;Jurkiewicz-Karnowska, 2011;Obolewski and Glińska-Lewczuk, 2011;Gallardo et al, 2012a). Increasing anthropogenic pressure on aquatic environments, such as deforestation, input of nutrients from agriculture and hydrotechnical works (Testa et al, 2010), directly and indirectly influence the trophic state of floodplain water bodies (Cabezas et al, 2009;Danehy et al, 2012). Considerable inflow of nutrients to those ecosystems is usually followed by an intensive growth of phytoplankton, decrease in water transparency and the elimination of stenotopic organisms (Mandaville, 2002).…”
Section: Introductionmentioning
confidence: 99%